Evaluación en la eficiencia de los sistemas de riego del cantón Chambo a través de indicadores de desempeño - Silva Yambay, Geovanna Alejandra (2025)
In Ecuador, water is an essential resource for agricultural production, as it influences productive, economic, and food security management. Chambo Canton is one of the main agricultural producers in the country because it offers a wide variety of products that supply local and national markets, making it an important agricultural area within Chimborazo. However, factors such as regional climate, inefficient distribution of water resources, and the current state of irrigation infrastructure affect the amount of water assigned to each system, leading to internal conflicts, losses, and a decrease in local production. Efficient water use mainly depends on proper planning and management, which are evaluated through technical mechanisms such as performance indicators proposed by the Ministry of Environment, Water, and Ecological Transition. In this project, the efficiency of the irrigation systems in Chambo Canton was evaluated using five performance indicators that also helped to understand the condition and operation of each irrigation system. This evaluation showed weaknesses mainly in the indicators of information identification and data collection, which remain at a “bad” level, since none of the irrigation boards had irrigation schedules or technical flow measurement equipment. On the other hand, the indicators of conveyance efficiency and social-organizational information management classified the boards as “regular,” because variables such as user knowledge and infrastructure conditions are not optimal.